Total synthesis of Met(10)-teixobactin - Gunjal, Vidya B.; Reddy, D. Srinivasa (Tetrahedron Letters, 2019)
The total synthesis of cyclic depsipeptide Met(10)-teixobactin in solution-phase is described. Teixobactin is a structurally and mechanistically novel antimicrobial peptidic natural product with very impressive activities against Gram-positive pathogens. It happens to possess an L-allo-enduracididine (End) residue as part of macrocyclic ring which is not readily accessible. In this report, we have used serine ligation strategy as the key step to prepare an analogue of teixobactin where End being replaced with a readily available amino acid methionine. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: antibiotic; Cyclic tetrapeptides; Serine ligation; Teixobactin

Teixobactin: a paving stone toward a new class of antibiotics? - Gunjal, Vidya B.; Thakare, Ritesh; Chopra, Sidharth; Reddy, D. Srinivasa (Journal of Medicinal Chemistry, 2020)
Antimicrobial resistance is a serious threat to human health worldwide, prompting research efforts on a massive scale in search of novel antibiotics to fill an urgent need for a remedy. Teixobactin, a macrocyclic depsipeptide natural product, isolated from uncultured bacteria (Elef theria terrae), displayed potent activity against several Gram-positive pathogenic bacteria. The distinct pharmacological profile and interesting structural features of teixobactin with nonstandard amino acid (three Damino acids and L-allo-enduracididine) residues attracted several research groups to work on this target molecule in search of novel antibiotics with new mechanism. Herein, we present a comprehensive and critical perspective on immense possibilities offered by teixobactin in the domain of drug discovery. Efforts made by various research groups since its isolation are discussed, highlighting the molecule's considerable potential with special emphasis on replacement of amino acids. Critical analysis of synthetic efforts, SAR studies, and the way forward are provided hereunder.